Intra-Sentential and Intra-Lexical Code Mixing in Nessie Judgeâ€™s YouTube Video Entitled â€œLagu Populer + Pesan Iblis Tersembunyiâ€ - I Made Drati Nalantha; Ni Komang Arie Suwastini; I Gusti Ayu Agung Dian Susanthi; Putu Wiraningsih; Ni Nyoman Artini (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
As a linguistic phenomenon, code mixing is common to be identified in language users. Furthermore, YouTube as one of the online platforms has become an environment rich with the use of code mixing. Considering that YouTube might influence the language use in its audience, the following study aimed to identify the use of code-mixing presented by Indonesian content creator named Nessie Judge. Following the qualitative analysis research from Miles, Huberman, & Saldana (2014), the recent study identified the types of code mixing as presented by Hoffman namely, Intra-sentential code-mixing and Intra-lexical code-mixing. The present study identified the use of code mixing type intra-sentential and -lexical uttered by the speaker. From 114 utterances made by Nessie Judge in her video, code-mixing was identified in 86 utterances, where 53 utterances belong to intra-sentential code mixing and 13 utterances belonged to intra-lexical code mixing. The analysis revealed that the use of code mixing might be rooted in the speakersâ€™ inability to find the equivalent words while discussing the video content. By looking at the number of the data percentage, intra-sentential code-mixing had more data than intra-lexical code-mixing meaning that the use of intra-sentential code-mixing was more common rather than intra-lexical code-mixing. It can be concluded because the speaker in the video inserts English words at the end of sentences or in the middle of sentences most of the time. The speaker on the video was clearly seen mixed Indonesian words with English words without changing the structure or context of the sentences.